Premature Hair Greying - Magnitude and Associated Factors: A cross-sectional study in a university in Mysuru - Kansal, Shrey; Bilimale, Anil S; Gopi, Arun; BV, Sushma (Indian Journal of Community Health, 2021)
Background: Premature hair greying (PHG) refers to the diffuse loss of hair color at an age earlier than that is generally accepted as physiological. Studies have found that it affects self-esteem and social life. Our efforts were to estimate the prevalence among students <25years and understand the associated factors. Design and Methods: A cross-sectional study using a simple random sampling technique was used to survey 358 students at a university in Mysuru. The data were analyzed using SPSS v22. The association and relationship of PHG with attributed risk factors and various socio-clinical factors have been analyzed using Chi-Square Test, Independent sample t-test, and Mann Whitney U-test. A p-value of less than 0.05 has been considered statistically significant. Results: In this study, the prevalence of PHG was 28.2%. We observed that PHG was associated with male gender, obesity, and positive paternal, maternal, and family history of PHG. The relation of PHG with lower dietary iron intake, tobacco smoking amount, and frequency was also found in this study. However, no association between PHG and psychological stress, alcohol consumption, dietary Vitamin B12, and D intake, shampoo, and oil usage frequency was found. Conclusion: We recommend that further studies should be done to check if weight reduction, smoking cessation, and maintenance of dietary iron adequacy can help in preventing PHG.